DISCOURSE ANALYSIS ON SBY’S INTERNATIONAL SPEECH TEXT: A STUDY ON CRITICAL LINGUISTICS - Meida Rabia Sihite; Sofia Idawati Lubis; Budi Setiawan (EXCELLENCE: Journal of English and English Education, 2021)
This study dealt with critical discourse analysis of SBY’s international speech text. The objective of this study was to describe social cognition, ideology, and social context used by SBY in his international speech. This study was conducted by applying descriptive qualitative design. The data of this study were taken from SBY’s international speech text. The texts were analyzed by using Van Dijk’s discourse analysis concept by classifiying the elements of the text into Van Dijk’s table. Based on the study, it was found that the social cognition used was the event social cognition, ideology used was the ideology of Pancasila democracy, and the social context used was the diction in accordance with the social status of the invited guests. It could be concluded that the diction chosen by SBY was adjusted to the social status of the guests who were present in the 19th ASEAN Summit and also represented interests of people.